Insights into ecological roles of uncultivated bacteria in Katase hot spring sediment from long-read metagenomics - Kato, Shingo; Masuda, Sachiko; Shibata, Arisa; Shirasu, Ken; Ohkuma, Moriya (Frontiers in Microbiology, 2022)
Diverse yet-uncultivated bacteria and archaea, i.e., microbial dark matter, are present in terrestrial hot spring environments. Numerous metagenome-assembled genomes (MAGs) of these uncultivated prokaryotes by short-read metagenomics have been reported so far, suggesting their metabolic potential. However, more reliable MAGs, i.e., circularized complete MAGs (cMAGs), have been rarely reported from hot spring environments. Here we report 61 high-quality (HQ)-MAGs, including 14 cMAGs, of diverse uncultivated bacteria and archaea retrieved from hot spring sediment (52ºC, pH 7.2) by highly accurate long-read sequencing using PacBio Sequel II. The HQ MAGs were affiliated with one archaeal and 13 bacterial phyla. Notably, 9 of the 14 cMAGs were the first reported cMAGs for the family- to class-level clades that these cMAGs belonged to. The genome information suggests that the bacteria represented by MAGs play a significant role in the biogeochemical cycling of carbon, nitrogen, iron, and sulfur at this site. In particular, the genome analysis of 6 HQ MAGs including 2 cMAGs of Armatimonadota, of which members are frequently abundant in hot spring environments, predicts that they are aerobic, moderate thermophilic chemoorganoheterotrophs, and potentially oxidize and/or reduce iron. This prediction is consistent with the environmental conditions where they were detected. Our results expand the knowledge regarding the ecological potential of uncultivated bacteria in moderately-high-temperature environments.